The nexus between financial literacy, risk perception and investment decisions: Evidence from Indonesian investors - Wendy Wendy (Investment Management & Financial Innovations)
Financial literacy is an essential factor for individuals or households in making investment decisions. However, the problem of insufficient financial literacy is still considered one of the factors limiting the creation of successful investments, especially in relation to risk perception. Some investors have financial losses due to their limited financial literacy, making inefficient investment decisions and implicating high-risk investment choices. Hence, this study aims to explore the interconnection between financial literacy, risk perception and investment decisions. Moderated regression analysis was used for 233 investors in Indonesia who completed financial management training. The results showed that financial literacy has a positive and significant impact on investment decisions, which means that it could be used to improve the quality of investment decisions. On the other hand, risk perception as a moderating variable weakened the impact of financial literacy on investment decisions; this confirmed the consistent results before and after financial training. Overall, financial literacy across three dimensions (knowledge, skills, and attitude) plays an important role in investors allocating more funds to investment instruments than respondent groups with lower financial literacy levels. In addition, the level of financial literacy also influences the choice of investment product.